Territórios paralelos. Os espaços residuais da área urbana do Porto - Nicoló Zingoni (2014)
The thesis concerns residual spaces: those spaces that are discarded, which are not in actual use and are characterised by an absence of meaning and as a consequence are not considered as relevant. Having said that, these places that have suffered the consequence of time, which are the result of various transformations and bare the evidence of their history, they can still become substance for new projects. Based on a careful study of the existing literature, this research is structured in three main axes. 1 Contemporary context Attention is spent on understanding how the territory in which we live transforms as well as on how the latters influence the city and its inhabitants. In understanding the relation between three apparently separate sets, such as cities, territory and landscape, through the following analysis we intend to identify the directions in which they evolve, examining the on-going fragmentation that is inherent in them. This process of fragmentation leads consequently to the increase of residual waste in the urban area. Ultimately, we justify how fragmentation and utilisation of the ground could be reabsorbed in order to create coherently a unique and cohesive space. 2. The residue From an etymological standpoint, we shall define what it represents and thus outline the characteristics of the residue in order to locate and to understand its different forms; distinguish the residue from what it is not, i.e. emptiness and ruin; understand the effects of time on the material. The present research concludes with a typological analysis on the nature of the residue, putting together sets of similar waste, discarded material and comparable (but always substantially different) elements. Waste indexing is preliminary instrumental in order to understand them, and therefor to control and use them as subject for new projects. 3 The project Starting from the intrinsic meaning of the term "project", we intend to develop a flexible methodology that will allow developing accordingly an integrated strategy based on the residue. Time and its influences on the various phases of project will be always taken in consideration. Moreover, complementary to the research on the topic, we shall examine temporary project and recycling practices in use. The present research ends with a project proposal for the urban area extending between the rivers Tinto and Torto including the adjacent space, in which we shall apply and verify the analysis developed so far.